(untitled) (Journal of Small Business Strategy (archive only), 2019)
The expression that “Innovation is the central issue in economic prosperity” (Michael Porter), encapsulates the importance of entrepreneurial strategy, which has been linked to firm growth, particularly through its dimensions of innovation and risk. Firm growth will increase its size, which in turn may affect the entrepreneurial strategy; a research area that has been under-studied. This research contributes to the literature by exploring the relationship between firm size and the entrepreneurial strategy. Findings support the hypothesis that in larger firms the owners pursue a strategy that tends to be higher in innovation but with reduced risk, while in smaller firms the owners pursue a strategy that is higher in risk but lower in innovation. Additionally, it was found that the firms’ Entrepreneurial Orientation (EO) is moderated by the organizational size; which supports the notion of bi-directional relationship between EO and organization attributes